Muhammad (s.a.w) he who enlightened humanity - Farooqui, Jamil (Radiance Viewsweekly, 2010)
Prophet Muhammad (may Allah bless and greet him) was the embodiment of truth, purity and righteousness. He was the fountain of eternal light that illuminated the minds and souls of human beings and enabled them to identify the path that leads to peace, prosperity, happiness and perfection. He saved humanity from disaster, destruction, oppression, suppression and the domination of evil forces. He preached submission to God, high standards of morality, good conduct, peace and tranquillity among human beings, virtuous living, decency and felicity. The Arabian society before him was characterised by tribal feuds and superiority, quarrels and bitter fighting among tribes, shedding of blood on petty matters, vice, barbarism and superstition. There was no respect for human beings particularly for weaker sections and the weaker sex. Women were considered commodities to be used for the pleasure of men. Even the birth of a girl was the subject of embarrassment and she was buried by the father himself. The entire condition was full of evil and malice. Oppression and violence were spread in every nook and corner. Thus, humanity was engrossed in darkness and ignorance, gasping in agony and groaning under torture, injustice, depravity and decadence. The Qur'an describes it as “mischief has appeared on land and sea because (the meed) that the hands of men have earned (30:41)”.